Acidosis-induced downregulation of hepatocyte mitochondrial aquaporin-8 and ureagenesis from ammonia - Molinas, Sara Maria (2015)
It has been proposed that during metabolic acidosis, the liver downregulates mitochondrial ammonia detoxification via ureagenesis, a bicarbonate-consuming process. Since we previously demonstrated that hepatocyte mitochondrial aquaporin-8 channels (mtAQP8) facilitate the uptake of ammonia and its metabolism into urea, we studied whether mtAQP8 is involved in the liver adaptive response to acidosis. Primary cultured rat hepatocytes were adapted to acidosis by exposing them to culture medium at pH 7.0 for 40 h. Control cells were exposed to pH 7.4. Hepatocytes exposed to acid medium showed a decrease in mtAQP8 protein expression (-30%, p<0.05). Ureagenesis from ammonia was assessed by incubating the cells with 15N-labeled ammonia and measuring 15N-labeled urea synthesis by nuclear magnetic resonance. Reduced ureagenesis was found in acidified hepatocytes (-31%, p<0.05). In vivo studies in rats subjected to 7-days acidosis also showed decreased protein expression of hepatic mtAQP8 (-50%, p<0.05) and reduced liver urea content (-35%; p<0.05). In conclusion, our in vitro and in vivo data suggest that hepatic mtAQP8 expression is downregulated in acidosis, a mechanism that may contribute to decreased ureagenesis from ammonia in response to acidosis.